FUNCTIONAL METATRANSCRIPTOMICS REVEALS A NOVEL MULTI METAL TOLERANT GENE OF NRAMP-FAMILY, ISOLATED FROM METAL-CONTAMINATED SOIL (Applied Biological Research, 2024)
The continuous release of heavy metal pollutants into soil through human  activities posesthreat to both macro- and micro-organisms within the ecosystem.  Functional metatranscriptomics is a robust method for discovering novel genes  associated with a particular biological process. In this study, functional meta transcriptomic approach was employed to isolate a gene from size-fractionated  cDNA libraries of micro-eukaryotes. The cDNA libraries were raised using  high-quality RNA from heavy metal-contaminated soil. The identified gene  aligned with Nramp (Natural resistance associated macrophage protein)  family. The gene, JMC-10, was submitted to GenBank under Accession No.  OR882126, and it encodes a protein with high sequence similarity to other  Nramp family members, including Smf1p, Smf2p, and Smf3p in  Saccharomyces cerevisiae. To study the function of JMC-10 gene, a series of  growth assays were conducted in yeast cells that either overexpressed JMC-10  or carried a deletion of gene. The study revealed the putative role of JMC-10 in  the transportation of divalent metal ions, including iron, manganese, zinc and  cadmium. Notably, the overexpression of JMC-10 was induced by exposure to  toxic levels of cadmium, suggesting it’s potential role in metal detoxification.  The study provides new intuitions into the roles of Nramp family in metal  homeostasis and highlights the potentiality of functional metatranscriptomics  for identifying new genes having crucial roles in complex biological processes.  Further, it may serve as a biomarker for identifying metal pollution.
Keywords: cDNA clone; metal homeostasis; metal transport; Nramp family; soil; micro-eukaryotes